ANALYSIS OF BEHAVIOR USING EMONEY WITH A TAM APPROACH(TECHNOLOGY ACCEPTANCE MODEL) - Wulandari, Indah Retno (Department of Management, 2020)
E-money is a non-cash electronic payment instrument that is currently growing rapidly in Indonesia. Based on Bank Indonesia data, there are already 39 banking and non-bank companies that have obtained permits to issue e-money products. This study aims to determine and analyze perceptions of the benefits of attitudes, perceptions of ease of attitudes, levels of trust in interests, attitudes affect interests, and interests influence behavior using E-Money.The population in this study were all e-money users in the Java Island region. Samples taken in this study are some e-money users in the Java Island region, amounting to 200 respondents. Sampling using non-probability techniques with convenience sampling method and research models were analyzed using Structural Equation Model (SEM), using the help of AMOS software.The results of this study indicate that the perception of benefits has a significant positive effect on attitude, the perception of ease has a significant positive effect on attitude, the level of trust has a significant positive effect on interest, attitude has a significant positive effect on interest and interest has a significant positive effect on behavior using emoney.